Prognostic significance of the advanced lung cancer inflammation index in metastatic small cell lung cancer: a retrospective analysis of 96 patients - Ürün, Müslih; Güner, Gürkan; Sezgin, Yasin; Uysal, Emre; Sakin, Abdullah; Kılıçkap, Saadettin (My University, 2024)
Background: The advanced lung cancer inflammation index (ALI) is regarded as a potential indicator of systemic inflammation. This retrospective study aimed to evaluate the prognostic role of the ALI in 96 patients with advanced small cell lung cancer (SCLC). Material/Methods: This retrospective study included 96 patients who were diagnosed with extensive stage SCLC in a single institution between 2016 and 2022. The formula for ALI is body mass index (kg/m2)×serum albumin (g/dL)/neutrophil to lymphocyte ratio. Patients were divided into low inflammation (ALI ≥32.5) and high inflammation (ALI <32.5) groups. Kaplan-Meier analysis and Cox proportional analysis were conducted to assess the association between the ALI and patient prognosis. Results: Median age was 61 (range: 41-82) years. Median follow-up was 9 months, and median overall survival (OS) was 10 months (95% CI: 7.75-12.45). A lower ALI score (ALI <32.5) was correlated with a poorer OS than was a higher ALI score (median OS 7 months for ALI <32.5 95% CI: 4.6-9.3 vs 15 months for ALI ≥32.5, 95% CI: 10.6-19.3, P<0.001). In the multivariate analysis, ALI score, Eastern Cooperative Oncology Group performance status, brain metastasis, and bone metastasis were identified as independent prognostic factors. Conclusions: ALI score is a substantial predictor of survival in SCLC as in other types of cancer types. Patients with a low ALI score have poorer survival. Assessment of ALI can identify lung cancer patients at high risk of poor prognosis and can be a useful prognostic marker in clinical practice.
Keywords: Inflammation; Lung; Lymphocytes; Neutrophils; Small Cell Lung Carcinoma